Genetic and Phenotype Analysis of a Chinese Cohort of Infants and Children With Epilepsy - Chuan, Zhang; Ruikun, Cai; Qian, Li; Shiyue, Mei; Shengju, Hao; Yong, Yuan; Haibo, Li; Neng, Xiao; Yong, Zhao; Huiqin, Xue; Weijia, Wang; Ling, Hui; et al. (Frontiers in Genetics, 2022)
Background: Childhood epilepsy is a common and diverse neurological disease. We conducted a genetic and phenotype analysis of a Chinese cohort of infants and children with epilepsy. Methods: We conducted a pedigree analysis of 260 Chinese patients with epilepsy onset during infancy or childhood by targeted next-generation sequencing and Sanger sequencing. Results: Among the 260 probands analyzed, a genetic diagnosis was established in 135 patients. One-hundred eighty-eight phenotypes were detected in those 135 positive/likely positive patients, 106 patients had more than two phenotypes, and 67 patients had more than three phenotypes. A total of 142 variants of 81 genes were detected among the positive/likely positive patients. Among these 142 variants, of which 89 of 67 genes were novel, 32 novel variants were categorized as “pathogenic”, 52 were categorized as “likely pathogenic” and five splicing variants were “Uncertain significance” according to the American College of Medical Genetics guidelines and InterVar software. Conclusion: Our findings extend the variant spectrum of genes related to epilepsy. Our results will be useful for genetic testing and counseling for patients with epilepsy.